STRATEGI PEMASARAN DALAM MENINGKATKAN MINAT JAMAAH PADA ERA DIGITAL DI KOTA BUKITTINGGI(Studi Kasus Pada Layanan Haji dan Umrah PT Sutra Tour Hidayah dan Travel Umrah) - Fani Amelia; Ariyun Anisah (BORJUIS: JURNAL OF ECONOMY, 2025)
The purpose of this research is to address the suboptimal use of digital marketing as a promotional medium in the digital era. Additionally, PT Sutra Hidayah Tour and Umrah Travel in Bukittinggi lacks sufficient resources in the marketing department. The objective of this study is to analyze the marketing strategies implemented by PT Sutra Hidayah to enhance awareness among Umrah pilgrims. This research employs a descriptive qualitative method, including interviews, observations, and documentation, which are then evaluated using SWOT analysis. The purpose of this analysis is to recognize and determine marketing strategies and develop alternative strategies to increase public interest The survey found that PT Sutra Hidayah Tour has several advantages, including the implementation of well- structured SOPs, attractive Umrah packages, collaborations with communities, and promotions through social media. Opportunities that can be leveraged include technological advancements, marketing expansion, a strategic location, and a better understanding of the millennial generation. Additionally, there are risks, including intense competition and low public trust. The results of the SWOT matrix recommend prioritizing the SO (Strengths and Opportunities) strategy, which utilizes internal strengths while optimizing external opportunities.